Municipal centers of southern France as a place of refuge for Polish refugees between 1939 and 1940 - Ambrochowicz-Gajownik, Anna (City and War, 2021)
The south of France has become an important hub for civilian and military refugees. The activities of the Polish authorities covered over 5000 refugees from Poland, as well as demobilized soldiers, of which there were 12 000. Evacuation to France was carried out by sea and land. From October 1939 until April 1940 31 727 people passed through the border crossings. By May 1940, 33 120 people had been evacuated. Special shelters and kitchens for refugees were created in various centers of southern France, and some were placed in hotels. Efforts were also made to create day-rooms and small workplaces. Moreover, all help was given to Polish soldiers and their families. Pre-war emigration was also taken care of. Gaining places for refugees would not be possible without the cooperation of local authorities. The Polish consular service operating until September 1940, as well as the Polish Red Cross delegations operating in Toulouse, Marseille and Nice played a key role in caring for refugees in this period. The defeat of France brought changes both for the Polish government and for refugees.